دور أجهزة دعم الاستثمار المركزية في تعزيز قدرات الاستثمار الوطني في ظل قانون 16-09 المتعلق بترقية الاستثمار - قسوري, فهيمة (Revue jurisprudence; Vol. 12 No 02 (2019): مجلة الاجتهاد القضائي, 2020)
اعتمدت الجزائر عبر مراحل النمو الاقتصادي على العديد من الاصلاحات الاقتصادية وصولا الى مرحلة اقتصاد السوق من خلال الانعاش الاقتصادي، وذالك في سعي للانفتاح على الاقتصاد العالمي من خلال جذب الاستثمار الذي أقره التعديل الدستوري2016 بموجب المادة 43:" حرية الاستثمار والتجارة معترف بها وتمارس في اطار القانون." ومن ثم فإن السياسة الجزائرية انتهجت في سبيل تعزيز الاستثمار الوطني أجهزة لدعم الاستثمار تابعة للادارة المركزية أنشأت بموجب الامر 01-03 المتعلق بتطوير الاستثمار الملغى بموجب القانون 16-09 المتعلق بترقية الاستثمار وأبقى بموجب المادة 37 منه على المواد 06 و18 و22 المتعلقة بهيئات مركزية وهي الوكالة الوطنية لتطوير الاستثمار والمجلس الوطني للاستثمار وإضافة إلى صندوق دعم الاستثمار ومجلس مساهمات الدولة والذي حددت المراسيم التنفيذية التنظيمية كيفية تدخل هذه الهيئات والاجهزة لدعم الاستثمار في ظل قانون 16-09. وعليه ندرس الموضوع من خلال اشكالية اساسية وهي: إلى اي مدى نجحت المنظومة التشريعية في تنظيم الأجهزة المركزية لدعم الاستثمار الوطني لتعزيزها الاستثمار الوطني ؟ الكلمات المفتاحية: الاستثمار الوطني، الاجهزة المركزية، الاصلاح الاقتصادي، ترقية الاستثمار.   Abstract: Algeria had adopted through the stages of economic growth on many of the economic reforms to reach the stage of a market economy through economic rehabilitation, the Champions Trophy in the quest of the openness to the world economy through attracting investment, which was approved by the constitutional amendment2016 under Article 43: Freedom of investment and trade is recognized and practiced in the framework of the law Therefore, the Algerian policy pursued toward the strengthening of the National Investment devices to support investment, belonging to the central administration established under the Ordinance 01-03 on the development of the canceled investment under Law 27-08 on the upgrade investment and kept under article 37 of the articles 06, 18 and 22 of the central bodies, the National Agency for Investment Development and the National Council for investment in addition to investment support fund and the contributions of the State, which defined the organizational executive decrees how to enter these organs and to support investment in under a law16-09. Thus, studying the subject through the basic problem, which is: To what extent succeeded legislative system in the organization of the central organs to support the national investment promotion in national investment? key words : National Investment . Central services . Economic Reform . Investment Promotion .